Gambaran Golongan Darah ABO-Rhesus dan Pola Sidik Jari Pada Mahasiswa Program Studi D-3 Teknologi Transfusi Darah STIKES Guna Bangsa Yogyakarta - St. Raihanun; Diani Mentari; Meyta Wulandari; Relita Pebrina (Journal of Health (JoH), 2019)
Human identification is the recognition of individuals based on some physical characteristics that are unique to individuals. Fingerprints are constant, individuality and form the most reliable criteria for identification. ABO-Rhesus Blood group is also one method used to identify someone, because blood type is inheritance. This research was conducted to see the description of ABO-Rhesus blood group and fingerprint patterns students D-3 Teknologi Transfusi Darah STIKES Guna Bangsa Yogyakarta. In this study using quantitative cross sectional descriptive research and blood group samples were taken using the slide method and fingerprint patterns were taken using the fingerprint method. In this study there were 78 samples, 58 females (74.36%) and 20 males (25.64%). The ABO blood group that is dominant is blood type O(35.90%), followed by blood group A(29.49%), B(28.21%), and AB(6.41%). The dominant Rhesus blood type is the positive Rhesus blood group. The percentage of fingerprint patterns in this study was loop 61.03%, whorl 37.56%, and arch 1.41%. The characteristics of the right and left hand fingerprint patterns have the same percentage of arch fingerprint patterns found on the index finger. Whorl fingerprint patterns are found on the ring finger. Loop fingerprint patterns are found on the little finger.